Pigment Production in Callus Culture of ‘Karandafi’ Red Sorghum (Sorghum bicolor (L.) Moench). A Probable Cure for Sickle Cell Anaemia - L. B. Hassan; I. S. Usman; A. Usman; H. Ibrahim; H. O. Ahmed; S. Mohammed (Recent Research Advances in Biology Vol. 8, 2021)
‘Karandafi’ is a landrace of sorghum with identified antisickling property and rich in 3-deoxyanthocyanidin but mutant in nature. This tends to limit large scale production of this important drug used for the treatment of sickle cell aneamia. Sorghum bicolor is very rich in various phytochemicals and its extract is used in combination with other medicinal plants to treat sickle cell anaemia. This work is designed to study the effect of different concentrations of hormone alone or in combination with elicitor on the production of pigment in Karandafi in vitro. Murashige and Skoog (MS) basal media was fortified with different concentrations of 2, 4-D (0, 2 and 4 mg/L) alone or in combination with 0.5 mg/L NAA or KN for callus induction using mature seeds as explant while MS media supplemented BAP (0-3 mg/L) alone or in combination with 1 mg/L KN, NAA or 50 mg/L yeast extract (Y.E) was used for pigment production. Data was collected on percentage callus formation, callus fresh weight, nature of callus induced, % shoot and root formation, number of root, shoot and root length. Highly significant difference was observed for all the traits measured. Media fortified with 2 mg/L 2,4-D alone or in combination with 0.5 mg/L NAA and KN are optimum concentrations of hormone that can be used for callus induction while better callus growth was obtained in the media fortified with 4 mg/L 2,4-D +0.5 mg/LKN (3.43 g). Pigment production was observed from the media fortified with BAP alone or in combination NAA, KN or yeast extract in Karandafi but with extraction and quantification the best treatment with highest content of 3-deoxyanthocyanindin can be determined.